Engaging Under‐Represented Adolescents and Young Adults in Cancer Research: A Qualitative Exploration of Lived Experiences and Engagement Strategies - Jenny Duong; Iqra Rahamatullah; Tristan Bilash; Caitlin Forbes; Sharon H. J. Hou; Brianna Henry; Perri R. Tutelman; Sheila N. Garland; Jackie L. Bender; Kaitlyn Hanson; Sapna Oberoi; Fiona S. M. Schulte (Cancer Medicine)
ABSTRACT Background Adolescents and young adults (AYAs; 15–39 years) diagnosed with cancer face unique challenges during and after treatment, which have implications for improving cancer care. However, AYA cancer research is limited by the under‐representation of those who identify as Indigenous, racialized, 2S/LGBTQIA+, and those living with disabilities. The aim of this project was to explore lived experiences and identify barriers and enablers to engagement, to inform strategies that facilitate the inclusion of under‐represented AYAs in cancer research. Methods Using a community‐based partnership research (CBPR) approach, under‐represented AYAs diagnosed with cancer, along with non‐patient advocates who serve this population, were recruited through social media, snowball, and convenience sampling. Semi‐structured interviews were conducted virtually through Zoom and analyzed using reflexive thematic analysis. Analyses were informed by collaborations with a patient partner and member‐checking feedback. Results Interviews were conducted with AYAs (n = 17) and non‐patient advocates (n = 2). Analyses generated three themes: (1) representation leads to empowerment, (2) person‐centered approaches are a prerequisite to building connections, and (3) structural contexts influence the impact of research. Discussion Our findings inform inclusive strategies for future studies to ensure the voices of all AYAs with cancer are represented in research. This study also highlights the importance of CBPR and the positive impact of knowledge derived from lived experiences in shaping research processes and outcomes.